Kingdom of the Netherlands-Aruba : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper analyzes sustaining potential growth in Aruba. As in the other Caribbean countries, there are growing concerns in Aruba about the slowdown in economic growth over the past two decades and the consequent tepid outlook for potential growth. Tackling such concerns requires identifying the underlying factors. This paper presents an overview of Aruba's economic growth performance since 1990, analyzes factors behind the slowdown, and discusses how potential growth can be sustained. It suggests that Aruba should aim to finance its renewable energy and other future growth initiatives sustainably.